Mexico Is Not Colombia Alternative Historical Analogies for Responding to the Challenge of Violent Drug-Trafficking Organizations - Paul, Christopher (RAND Corporation, 2014)
Despite the scope of the threat they pose to Mexico's security, violent drug-trafficking organizations are not well understood, and optimal strategies to combat them have not been identified. While there is no perfectly analogous case from history, Mexico stands to benefit from historical lessons and efforts that were correlated with improvement in countries facing similar challenges related to violence and corruption